2022
DOI: 10.3389/fphar.2022.909168
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of commonly used cardiovascular drugs in inhibiting vonoprazan metabolism in vitro and in vivo

Abstract: As a novel acid-suppressing drug, vonoprazan shows the potential to replace traditional proton-pump inhibitors. With its widespread use, some adverse effects that require further study have emerged due to drug–drug interactions. Our study is the first experiment that evaluated the drug–drug interactions of eleven common cardiovascular drugs that inhibit vonoprazan metabolism in vitro and in vivo. Rat liver microsome incubation and molecular simulation docking were applied to explore the inhibition mechanism. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Molecular docking simulations (Figure 7 ) were carried out to validate the compound‐target associations, using the methods previously described. 20 , 21 The BE less than −5.0 kcal/mol indicates a strong binding interaction between the small molecule and target protein. As shown in Figure 7a,b , SA and poziotinib bind closely with CYP3A4 in the same binding pocket, with BE of −6.8 kcal/mol and −9.2 kcal/mol, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular docking simulations (Figure 7 ) were carried out to validate the compound‐target associations, using the methods previously described. 20 , 21 The BE less than −5.0 kcal/mol indicates a strong binding interaction between the small molecule and target protein. As shown in Figure 7a,b , SA and poziotinib bind closely with CYP3A4 in the same binding pocket, with BE of −6.8 kcal/mol and −9.2 kcal/mol, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular docking simulations (Figure 7) were carried out to validate the compound‐target associations, using the methods previously described 20,21 . The BE less than −5.0 kcal/mol indicates a strong binding interaction between the small molecule and target protein.…”
Section: Resultsmentioning
confidence: 99%
“…6,8 Specifically, vonoprazan is metabolized oxidatively by multiple liver CYP450 enzymes (eg, CYP3A4, CYP2B6, and CYP2D6) and nonoxidatively by sulfotransferase; however, CYP3A4 is the primary metabolic pathway. 9,10 Interference with the metabolism of vonoprazan by clarithromycin, a potent inhibitor of CYP3A4, provides corroborative evidence that the major metabolic disposition pathway of vonoprazan occurs via CYP3A4. 11 Bismuth absorption and elimination have been studied by analyzing its PK in human plasma and urine, which showed that <1% of the administered dose is absorbed, and renal excretion is the primary route of bismuth elimination.…”
mentioning
confidence: 89%
“…Moreover, vonoprazan is not primarily metabolized by CYP2C19; therefore, CYP2C19 polymorphism has limited influence on the acid‐inhibitory effect of vonoprazan 6,8 . Specifically, vonoprazan is metabolized oxidatively by multiple liver CYP450 enzymes (eg, CYP3A4, CYP2B6, and CYP2D6) and nonoxidatively by sulfotransferase; however, CYP3A4 is the primary metabolic pathway 9,10 . Interference with the metabolism of vonoprazan by clarithromycin, a potent inhibitor of CYP3A4, provides corroborative evidence that the major metabolic disposition pathway of vonoprazan occurs via CYP3A4 11 …”
mentioning
confidence: 99%
“…M-III derives from the oxidation of the secondary amino group to the nitron form, whereas M-IV-Sul derives from the N-sulfation of the secondary amino group, following hydroxylation of the fluorophenyl ring [111]. Recent molecular modelling studies suggested that CYP2B6 may contribute to vonoprazan metabolism more than CYP3A4 [112]. Moreover, vonoprazan inhibits CYP2B6 and CYP3A4/5 [113].…”
Section: Vonoprazanmentioning
confidence: 99%